KUNJUNGAN RUMAH SEBAGAI STRATEGI PENINGKATAN PELAYANAN KESEHATAN UNTUK KELUARGA RAWAN DI KOTA MATARAM (WILAYAH KERJA PUSKESMAS KARANG PULE) - Yatik Krisliani; Mubasysyir Hasanbasri (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2021)
Background: The Government of Indonesia has adopted the Healthy Indonesia Program with a Family Approach (PIS-PK) as a strategic step to assist home visit services for vulnerable populations. Current PIS-PK research or home visits relate to how home visits result in mapping of health conditions. Mataram city is included in the vulnerable category. For this reason, a strategy is needed to address vulnerable communities in the city of Mataram by conducting a home visit program. Objective: To examine the home visit program for vulnerable or vulnerable communities within the puskesmas area and how such home visits will strengthen the improvement of these health services. Methods: The research method used a qualitative descriptive approach with data collection using interview guidelines and data analysis using descriptive analytic. The subjects in this study were nurses or midwives who had done home visits, heads of puskesmas, heads of home visit programs and people who received home visit services. Results: Home visits were carried out to all families in the working area of the Karang Pule Health Center, both to families with health problems and those without health problems. This caused a lack of focus for health workers in providing home visit services to vulnerable families because they do not prioritize which families to visit. Antenatal care services for pregnant women were not carried out during home visits. In addition to home visits, services for pregnant women are carried out by telephone with a process through cadres to be informed to the puskesmas midwife. The services provided during home visits are health education, education and care for families who have health problems. Conclusion: Home visit service to all families in each region is an ineffective program because home visits should be aimed at prioritized families, specifically families who are vulnerable, both in terms of health and vulnerable in the use of health service facilities.